SOCIO-CULTURAL AND PSYCHOLOGICAL PROBLEMS OF FOREIGN STUDENTS ADAPTATION IN A HIGHER SCHOOL - Rudenko, N.; Руденко, Н. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The issues related to socio-cultural and cross-cultural adaptation of foreign students have been analysed, the indicators of psychological adaptation have been identified, some aspects of their psychological adjustment have been studied, the concept of «culture shock» in the process of psychological adaptation to the cultural differences between countries has been analysed.
СОЦИОКУЛЬТУРНЫЕ И ПСИХОЛОГИЧЕСКИЕ ПРОБЛЕМЫ АДАПТАЦИИ ИНОСТРАННЫХ СТУДЕНТОВ В УСЛОВИЯХ ВУЗА
СОЦІОКУЛЬТУРНІ ТА ПСИХОЛОГІЧНІ ПРОБЛЕМИ АДАПТАЦІЇ ІНОЗЕМНИХ СТУДЕНТІВ В УМОВАХ ВНЗ
Keywords: higher education; international students; culture shock; socio-cultural adaptation; psychological adaptation; высшее образование; иностранные студенты; культурный шок; социокультурная адаптация; психологическая адаптация; вища освіта; іноземні студенти; культурний шок; соціокультурна адаптація; психологічна адаптація; 378.147